O atendimento por instituição pública de saúde: percepção de famílias de doentes com câncer - Rodrigues, Juliana Stoppa Menezes; Ramdohr Sobrinho, Ellen Cristine; Toledo, Maria Luíza Vasco De [UNESP]; Zerbetto, Sonia Regina; Ferreira, Noeli Marchioro Liston Andrade (Centro Brasileiro de Estudos de Saúde, 2013)
This study aimed to analyze how the families of cancer patients perceived the treatment provided at a specialist public outpatient clinic, using Bardin's method of Content Analysis. Seven families consisting of fourteen family members were interviewed. They underlined doctor-patient relationship, judging it to be impersonal and superficial, resulting in a lack of security and trust. Families try to to participate but feel undervalued and excluded from the care. Necessary information that they are not given is sought in the media, while comfort is achieved through religious or spiritual practices. Health care training must encourage professionals to view the family as a unit of care, aligning training to different modes of health care.

Este estudo objetivou analisar como as famílias de pessoas com câncer perceberam o atendimento prestado pelos profissionais de um ambulatório público especializado, utilizando Análise Temática de Bardin. Foram entrevistadas 7 famílias, totalizando 14 membros familiares que, em seus discursos, enfatizaram a relação médico-paciente, avaliando-a como impessoal e superficial, gerando insegurança e descrença. A família procura participar, mas sente-se pouco valorada e excluída do cuidado. As informações necessárias e não recebidas são buscadas na mídia, e o conforto é alcançado na espiritualidade. A formação dos diversos profissionais da saúde precisa estimular o olhar para a família como unidade de cuidado, articulando formação e modos de cuidar em saúde.
Treatment by a public health care institution: from the perspective of the families of cancer patients
Keywords: Pessoal de saúde; neoplasias; família; Health Personnel; neoplasms; family